(untitled) (Research, Society and Development, 2020)
Snacks are extruded products made from corn, and for this reason several studies have sought the partial or total replacement of corn by other ingredients with higher nutritional value. We partially replaced the corn grits by shrimp atomized powder, aiming to increase the protein values in the final product, and analyze the chemical and physical characteristics of the snacks made with shrimp powder. The extruded products were obtained by partially replacing the grits by shrimp powder in the following proportions: 2, 4, 8 and 16%. The addition of shrimp powder increased the protein content from 2 to 9% in the snacks, in comparison with the control. The hygroscopicity of the product was not affected by the addition of shrimp powder. However, the increasing concentration of shrimp powder, in the formulations, decreased the expansion and increased the product hardness. The snacks developed in this study are protein products, crispy and showed dark color, becoming an attractive product for the consumer who seeks products with higher nutritional value.